Respiratory Status in Children and Exposure to Animal Allergens-The Problem of Reverse Causality in Cross-Sectional Studies - Agata Wypych-Ślusarska; Karolina Krupa-Kotara; Klaudia Oleksiuk; Joanna Głogowska-Ligus; Jerzy Słowiński (MDPI AG, 2024)
Background: Some epidemiological studies suggest that early exposure to animal allergens during infancy reduces the risk of bronchial asthma in school-age children. However, the observed associations in some cases may be an effect of the study used (epidemiological observational studies, especially a cross-sectional study) and indicate reverse causality. Aim: This study aimed to determine the association between exposure to animal allergens and the prevalence of respiratory diseases, including bronchial asthma, considering the potential impact of reverse causality on the observed relationships. Material and methods: An analysis of data from a cross-sectional epidemiological study conducted in 2020 involving 3237 primary school students aged 7-15 years in the Silesian Province (Southern Poland) was carried out. The parents of students completed a questionnaire based on The International Study on Asthma and Allergies in Childhood (ISAAC). The relationship between the occurrence of chronic cough, wheezing, and dyspnea in the last 12 months, night waking due to dyspnea, and asthma in the presence of pets was assessed. Exposure to animal allergens was determined by answering the question, "Are there any furry or feathered animals in the home?" with three response options: "yes; they have been in the past; no" (Scenario 1). For the analyses and to reveal a potential reverse causality effect, the last two response categories regarding pet ownership were combined to form a "no" category in Scenario 2, and the first two answers were combined into a "yes" category in Scenario 3. A chi-square test was used to assess the relationship between variables, and a statistical significance level of p < 0.05 was adopted. Results: Chronic cough affected 9.5% of children, wheezing in the last 12 months-9.2%, night waking due to dyspnea-5.8%, dyspnea in the last 12 months-4.8%, bronchial asthma-9.2%. Analysis considering the category of having or not having pets (yes vs. no) showed that bronchial asthma was statistically significantly more common in children who did not have pets at home (10.9% vs. 7.9%, p = 0.002). A similar situation was observed for wheezing in the past 12 months (10.7% vs. 8.1%; p = 0.01) and nocturnal awakening due to dyspnea (6.8% vs. 5.1%, p = 0.03). No statistically significant differences were observed for the other symptoms. Analysis by time of pet ownership (a. present; b. present but in the past; c. not present) highlighted similar relationships. Asthma (a. 7.7% vs. b. 13.4% vs. c. 7.7%; p = 0.004), wheezing in the past 12 months (a. 8.1% vs. b. 8.9% vs. c. 10.9%, p = 0.03) and night waking (a. 5.0% vs. b. 4.5% vs. c. 7.1%; p = 0.04) were more common in children without pets and those who had owned pets in the past. The highest proportion of children with asthma was in homes where pets were present in the past. Conclusions: Analyses indicating a relationship between a higher prevalence of asthma and some respiratory symptoms, and the absence of pets cannot be considered as a casual association. The analysis conducted did not reveal a reverse causality effect. The results of observational epidemiological studies, especially a cross-sectional study, should always be interpreted with caution, considering possible distortions and conclusions drawn.